HUNGARIAN CONSTITUTIONALISM: FROM SÓLYOM’S HUMANISM TO AUTOCRATIC LEGALISM IN THE CARPATHIAN BASIN - Edstron S. Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This research investigates Hungary’s metamorphosis into a laboratory of “reverse constitutional engineering,” where formally legal reforms were instrumentalized to erode the substance of the Rule of Law. It analyzes the transition from the judicial humanism of the Sólyom era to the current “autocratic legalism,” characterized by the capture of the Constitutional Court and its conversion into a mechanism of illiberal legitimation. In an unprecedented comparative perspective, the study contrasts Budapest’s institutional erosion with the “combat constitutionalism” of the Brazilian Supreme Court, which activated mechanisms of militant democracy to contain authoritarian populism. It concludes that democratic survival requires the implementation of an architecture of institutional “antifragility”; otherwise, the legal system becomes the very tool of its own destruction.